Transformation of Islamic Religious Education Streams in the Digital Era: A Systematic Literature Review on the Formation of Halal Awareness, Behavior, and Perception of Halal Transparency - Nadya Kamilia; Fatkhur Rokhman; Muhlisin Muhlisin; M Sugeng Sholehuddin (MASI Mandiri Edukasi, 2026)
The fragmentation between Islamic religious education, halal consumption behavior, and halal supply chain transparency creates a conceptual gap that hinders the development of a sustainable halal ecosystem in the digital era. This study aims to develop an integrative conceptual model that connects Islamic educational streams, digital transformation, internalization of Qur'anic values, halal awareness, halal consumption behavior, and perceptions of halal transparency within a cohesive theoretical framework. A Systematic Literature Review (SLR) design based on the PRISMA 2020 protocol was applied, analyzing 78 final articles selected from 487 identified in Scopus, Web of Science, Google Scholar, and DOAJ. Data were analyzed through narrative synthesis, VOSviewer bibliometric mapping, and NVivo 14 thematic analysis. Results showed that digital contextual approaches in Islamic Religious Education yield stronger internalization of Qur'anic values (d = 0.61); 81.6% of studies confirmed that halal awareness positively influences purchasing decisions; and blockchain-based transparency increases consumer trust contingent on halal literacy rooted in Islamic education.